Bioactive compounds from tropical fruit by-products: Extraction, characterization and therapeutic potential - Niza Otero-Guzman; Ricardo Andrade-Pizarro (Journal of Agriculture and Food Research)
The processing of tropical fruits generates large amounts of residues, such as peels or seeds, with great nutraceutical potential due to their high content of bioactive compounds: polyphenols, carotenoids, anthocyanins, flavonoids, tannins, and phenolic acids with antioxidant, anti-inflammatory, antimicrobial, anticancer and anti-obesity properties. However, there are several challenges associted with the efficient extraction and accurate characterization of these compounds, including the complexity of plant matrices, variability in compound polarity, and the need for scalable, eco-friendly methods that preserve their bioactivity. This review highlights the bioactive composition, the most important and studied therapeutic properties of the by-products of different tropical fruits such as mango, pineapple, and avocado, and the main extraction, identification, and characterization techniques of these compounds. A scientific surveillance analysis of studies published on the last 5 years revealed a 67.6 % increase in research activity, with a growing emphasis on green extraction technologies—such as ultrasound-assisted, microwave-assisted, and supercritical fluid extraction— and the use of emerging solvents like natural deep eutectic solvents. Moreover, there is increasing interest in optimizing extraction conditions and in validating the functional potential of bioactive compounds through in vitro digestion and bioavailability assays. These trends underscore the strategic relevance of tropical fruit by-products as a sustainable source of functional compounds. The integration of clean technologies, optimization and scale-up strategies, and advanced analytical methods supports their valorization and promotes the development of high value-added nutraceuticals aligned with circular economy principles and public health objectives.